Synthesis and biological evaluation of 9-N-oxamyl sialosides as siglec-7 ligands - Prescher, Horst; Gütgemann, Stephan; Frank, Martin; Kuhfeldt, Elena; Watzl, Carsten; Brossmer, Reinhard (Bioorganic & medicinal chemistry, 2015)
Siglecs (sialic acid recognizing immunoglobulin like lectins) are a family of lectins with specificity for sialic acid containing carbohydrates. Synthetic sialic acid derivatives with high affinity proved useful to unravel the biological role of the ligand binding domain, although many of their functions in immunity remain unknown. Here we present design, synthesis, affinity evaluation and molecular modeling of novel 9-N-oxamoyl modified sialosides as Siglec-7 ligands.
Gesehen am 09.07.2020